Pathological and Incidental Findings in 403 Taiwanese Girls With Central Precocious Puberty at Initial Diagnosis - Chiu, Chiao-Fan; Wang, Chao-Jan; Chen, Yi-Pin; Lo, Fu-Sung (Frontiers in Endocrinology, 2020)
Background: Whether girls with central precocious puberty (CPP) should undergo routine brain magnetic resonance imaging (MRI) to identify potential intracranial pathology is controversial. Aims: To evaluate the brain MRI results of girls with CPP. Methods: This retrospective study obtained data from pediatric endocrine clinics at Chang Gung Children’s Hospital. From 1997 and 2017, 403 girls were consecutively diagnosed with CPP. After the exclusion of patients with a history of CNS insults or associated neuropsychiatric symptoms, we studied the prevalence of brain abnormalities in 251 girls with CPP who received detailed MRI examinations of the hypothalamus and pituitary area. We also recorded the demographic data of the participants, including the onset of puberty; initial pubertal status; height; weight; uterus and ovary sizes; and basal LH, FSH, estradiol levels, and the response to GnRH stimulation test. Results: Among the 251 girls with CPP, we observed no brain alterations in 190 (75.70%), abnormalities in the hypothalamic-pituitary (H-P) area in 54 (21.51%), and abnormalities in the non-H-P area in 7 (2.79%). Among the 54 patients that had H-P lesions, we noted pathological findings related to CPP (hypothalamic hamartoma) in only one(0.4%) girl. We also identified incidental findings in the other girls with H-P lesions, including non-functioning pituitary microadenomas (12.35%), pituitary pars intermedia cysts (4.38%), Rathke’s pouch cysts (1.99%), pituitary hypoplasia (1.59%) and pineal gland cysts (0.8%). The patients that had non-H-P lesions were found to have arachnoid cysts (1.59%), Chiari I malformation (0.4%), prepontine nodule (0.4%) and choroidal fissure cyst (0.4%). Of all the patients with brain lesions, 45 (73.77%) underwent regular MRI follow-up. While none of the H-P and non-H-P lesions showed progression, 19.67% of these regressed during the follow-up. None of the participants exhibited other hormonal abnormalities or underwent surgery. Conclusion:  The prevalence of true pathological brain lesions related to CPP in girls without prior symptoms or signs of CNS lesions was low (0.4%). None of the girls with intracranial lesions required further intervention besides the GnRH agonist treatment. These data question the routine use of brain MRI in all girls with CPP, especially in those who are healthy without neurologic symptoms.